DIGITAL LEADERSHIP DI TENGAH TRADISI: TANTANGAN KEPEMIMPINAN KIAI DALAM MENGELOLA RUANG SIBER (CYBER) DAN LITERASI DIGITAL SANTRI DI ERA DISRUPSI - Siti Aimah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to analyze in depth the challenges and strategies of Kiai Leadership (Digital Leadership) in managing Cyberspace and improving the Digital Literacy of students in Islamic boarding schools that are steeped in tradition, along with the massive era of technological disruption. Using a qualitative approach with a case study type, data were collected through in-depth interviews with Kiai, the Board of Trustees, and student representatives, as well as participatory observation of the implementation of digital policies. The results of the study show that the Kiai Leadership of Darussalam Blokagung Islamic Boarding School uses the Hybrid Khittah Model to respond to digital disruption. Kiai establishes moral values ??(Muhafazhah), while technical implementation is delegated. The main challenge, namely the conflict between the Khidmah of the students and the attraction of Cyberspace (FOMO), is overcome through strict discipline (Ta'zir) and spiritual strengthening. Kiai also transforms the traditional value of Tabayyun into the foundation of Digital Literacy to form cyber ethics. This model successfully balances the preservation of values ??with controlled technology adoption, contributing to the theory of Contextual Transformational Digital Leadership. Keywords: Digital Leadership, Cyberspace, Digital Literacy. This research contributes theoretically to Contextual Transformational Digital Leadership in faith-based educational institutions. Practically, it presents the Hybrid Khittah Kiai Leadership model that successfully balances the preservation of traditional values ??(Tabayyun → Digital Literacy) with controlled technology adoption